Research Trend of Learning Media in Fashion Education in Indonesia - Utami, Rima Agustia; Nelmira, Weni; Chairani, Vici Syahril; Utami, Resti (Indonesian Journal of Educational Research and Review, 2025)
The development of learning media in fashion education still faces limitations, particularly in the integration of digital technology to support the teaching and learning process. This condition highlights the urgency of examining research trends related to learning media in order to gain a comprehensive understanding of development directions that are relevant to current educational needs. This study aims to analyze the research trends of learning media in the field of fashion education through a bibliometric approach. The research employed a quantitative descriptive method with a bibliometric analysis design. Data were obtained from 500 articles collected through the Google Scholar database for the period 2010–2024 using the Publish or Perish application. The articles were then screened and re-verified with the assistance of Excel and Mendeley, resulting in 328 eligible articles for analysis. Data were analyzed using VOSviewer to map research trends based on keywords, publications, and inter-topic connections. The findings indicate a significant increase in the number of publications, with the peak occurring in 2023. VOSviewer analysis identified eight clusters with 104 keyword links, in which the dominant keywords include “learning media,” “video tutorial,” “e-module,” and “learning outcomes.” This study concludes that bibliometric exploration provides valuable contributions to the development of more innovative, interactive, and effective learning media, while serving as a strategic reference for enriching practices in fashion education in the future.